Growth dynamics of ‘Imola’ poplar clone (Populus ×canadensis Mönch) under different cultivation inputs - Bergante, Sara; Facciotto, Gianni; Marchi, Maurizio (Annals of Silvicultural Research, 2020)
The influence of environmental drivers and management strategies on crops growth is a focal point to deal with the potential impact of the climate changes on forest yields. The main aim of this study was to evaluate the effect of irrigation and fertilization on growth dynamics of ‘Imola’ clone, an elite poplar crossed from Populus deltoides Bartr. and Populus nigra L. for short rotation coppice purposes. Using a split-plot design with three replications, two treatments were applied (irrigation and fertilization) with two levels each one: ‘no’ and ‘yes’; 4 theses were considered: irrigation-only (IRR), fertilization-only (FRT) and the irrigation with fertilization (IRF) and control (CRT). At the end of the first 5-year cycle the average yield, in dry matter, was 36.8 Mg ha-1 for non-irrigated plots and 80.8 Mg ha-1 for irrigated plots. While no statistical evidence was detectable for fertilization treatment, a Linear Mixed Model analysis applied to data highlighted the Summer (June-August) as key season for the irrigation of trees. Conversely, interaction between irrigation and fertilization negatively affected growth in the same period. Overall, this trial demonstrated a low impact of fertilization on growth dynamics. Water availability was confirmed as the most important factor for poplar growth, in such site, focusing on the importance of studying alternative, less impacting methods for irrigating such crops.